Hemophagocytic lymphohistiocytosis occurring after liver transplantation: A case series and review of the literature. Issue 8 (8th July 2021) - Chesner, Jaclyn; Schiano, Thomas D.; Fiel, M. Isabel; Crismale, James F.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening disease characterized by excessive inflammation and tissue destruction due to a dysregulated immune response. Its secondary form is most commonly triggered by viral infection or malignancy. There have previously been 11 cases of acquired HLH described following liver transplantation in adult transplant recipients, most occurring within the first year following transplantation. Herein, we describe two cases of HLH in liver transplant recipients that both occurred remotely following transplantation. In the first case, HLH was thought to be triggered by the development of a post‐transplant lymphoproliferative disorder in a patient who was initially diagnosed with recurrent autoimmune hepatitis. In the second, it was thought to be triggered by a newly acquired human herpesvirus‐8 infection. In both cases, the syndrome was not recognized until treatment for the initial putative diagnoses was unsuccessful. Despite treatment, both patients unfortunately died from multiorgan failure. HLH in the post‐liver transplant setting is likely under‐recognized and has a high mortality; early diagnosis and intervention may lead to improved outcomes.